Fragile-X Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A characteristic epileptogenic EEG pattern is described in five of 12 male subjects with fragile-X syndrome evaluated at the Instituto Oasi, via C. Ruggero, Troina, Italy, and Clinica Neurologica, II Universita Roma and Bologna, Italy.